2008
DOI: 10.1074/jbc.m804090200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the C-terminal Truncation on the Functional Cycle of Chaperonin GroEL

Abstract: To elucidate the exact role of the C-terminal region of GroEL in its functional cycle, the C-terminal 20-amino acid truncated mutant of GroEL was constructed. The steady-state ATPase rate and duration of GroES binding showed that the functional cycle of the truncated GroEL is extended by ϳ2 s in comparison with that of the wild type, without interfering with the basic functions of GroEL. We have proposed a model for the functional cycle of GroEL, which consists of two rate-limiting steps of ϳ3-and ϳ5-s duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 35 publications
1
11
1
Order By: Relevance
“…In this case, the rate of ATP hydrolysis into ADP-Pi in the presence of DM-MBP is 1/(1/k FB-I þ 1/k BF-I þ 1/k 1 ) ¼ 0.32 s 21 or 1/(1/k FB-I þ 1/k BF-I þ 1/k 2 ) ¼ 0.28 s 21 . These values are close to the values estimated from biochemical studies in the presence of foldable SP, 0.3120.36 s 21 [35,43]. Note that the biochemically determined rate of ATP !…”
Section: Discussionsupporting
confidence: 85%
“…In this case, the rate of ATP hydrolysis into ADP-Pi in the presence of DM-MBP is 1/(1/k FB-I þ 1/k BF-I þ 1/k 1 ) ¼ 0.32 s 21 or 1/(1/k FB-I þ 1/k BF-I þ 1/k 2 ) ¼ 0.28 s 21 . These values are close to the values estimated from biochemical studies in the presence of foldable SP, 0.3120.36 s 21 [35,43]. Note that the biochemically determined rate of ATP !…”
Section: Discussionsupporting
confidence: 85%
“…A cysteine-introduced GroES variant (ES98C) (17) modified with Alexa Fluor 488 and biotin (termed A488bio-ES) was immobilized in ZMWs through a biotin-streptavidin linkage. We have previously confirmed that the immobilization of GroES does not perturb the binding to GroEL (21). Wild-type GroEL was fluorescently labeled with Cy5 (termed Cy5-EL).…”
Section: Resultsmentioning
confidence: 88%
“…A flow cell was constructed from a glass slide and coverslip with ZMWs separated by two spaces of ϳ50-m thickness (Lumirror 50-S10; Toray Industries, Tokyo, Japan). A488bio-ES was immobilized on to the bottom of the ZMWs through biotinylated bovine serum albumin and streptavidin as previously described (21). Experimental results shown in this paper were obtained in HKM buffer containing 50 nM Cy5-EL, 300 nM Cy3-labeled t-ES 98C (Cy3-ES), 2 mM ATP, 10 M reduced LA (rLA), an ATP-regeneration system (5 mM phosphoenolpyruvate and 10 g/ml pyruvate kinase), an oxygen scavenging system (0.45% (w/v) D-glucose, 50 units/ml glucose oxidase, and 50 units/ml catalase), 7 mM dithiothreitol, and 2 mM Trolox.…”
mentioning
confidence: 99%
“…S1A). Previous studies show that in forming a complex with GroEL, GroES inhibits the ATP hydrolysis rate of GroEL by ϳ50% (16,21,45,46). Neither GroESI25D nor GroESL27D variants altered GroEL ATP hydrolysis significantly (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%